Evaluasi Dampak Investasi Sosial: Analisis SROI pada Intervensi Dana Hibah Penelitian dan Pengabdian Akademisi Perguruan Tinggi Ke Bisnis Sosial: (Studi Kasus Akademisi Universitas Ma Chung ke Kelompok Tani Kopi Republik Tani Mandiri) - Audito Aji Anugrah; Nabila Maulina Delia Aliyanti (Fakultas Ekonomi Program Studi Akuntansi Universitas 45 Surabaya, 2024)
This study evaluates the effectiveness of the Republic Tani Mandiri (RTM) social business program using the Social Return on Investment (SROI) approach. The research focuses on the RTM Coffee Farmers Group, an initiative in coffee agriculture. A mixed-method approach with a subsequential exploratory design was employed. The analysis reveals that an initial investment of IDR 279,756,965 has not yet yielded positive short-term results, with an SROI ratio of 1:0.25. This indicates that each IDR 1 invested generates a social, economic, and environmental impact valued at IDR 0.25. Although this ratio is lower than anticipated, the program’s social and economic impacts remain significant. Positive changes were observed among coffee farmers in Desa Kucur, who experienced improved coffee quality and selling prices with support from Universitas Ma Chung. However, to ensure sustained benefits, ongoing support and strategic adjustments are necessary. The findings are expected to encourage continued support for similar initiatives in the future.